The geology and geochemistry of the Glentig, Swaershoek and Alma Formations in the Limpopo Province, South Africa - Makulana Mulalo Melton (My University, 2021)
The Glentig, Alma and Swaershoek Formations were deposited after the emplacement of the Bushveld igneous complex (BIC). The sediments accumulated in what is termed as the proto-basin of the Waterberg Group. The Glentig Formation is an unconformity-bounded formation that is overlain by the Swaershoek and Alma Formations of the Waterberg Group. This study revisited the stratigraphy and put perception on the petrography, lithofacies, provenance, paleoweathering, tectonic setting and source rock characteristics of the lower parts of Waterberg Group (Swaershoek and Alma Formations) and Glentig Formation. The methodologies employed in achieving the aforementioned goals include stratigraphical analysis, petrographical and modal composition analyses, lithofacies analysis and geochemical analysis. In the study area (northeast of Modimolle town), the Glentig Formation lies or bounded between the Swaershoek Formation and Schrikkloof Formation of the Rooiberg Group. The Glentig, Swaershoek and Alma Formations attained a maximum thickness of about 400 m, 300 m and 190 m, respectively. Based on the stratigraphical analysis, the Swaershoek, Alma and Glentig Formations can be correlated. The basis for the correlation rests solemnly on the similarities in the lithological characteristics that can be found in the three formations. Six facies were identified based on lithofacies analysis. The lithofacies are grouped into 2 facies association (FA1 and FA2). The two facies associations are FA1: Conglomerate and massive sandstone, and FA2: Cross-bedded sandstone, and planar cross-bedded sandstone. Sedimentological characteristics of the identified facies associations are interpreted as debris flow, and longitudinal and transverse bars (fluvial channel deposits). Petrography and modal composition analyses indicate that the detrital components of the sandstones are dominated by monocrystalline quartz, feldspar and lithic fragments. The sandstones of the Swaershoek, Alma and Glentig Formations can be classified as subarkosic arenite and lithic arkosic arenite. Also, provenance analysis indicates that the sandstones are derived from both felsic igneous provenance and intermediate igneous provenance. The modal composition analysis and geochemical tectonic setting discrimination diagrams show that the sediments are from both the passive and active continental margin tectonic settings. Also, the geochemical data of major and trace elements suggested that the studied formations have been derived from the same provenance source area. The indices of weathering indicated that the studied rocks have been subjected to moderate to the high degree of chemical weathering. Keywords: Geology, geochemistry, Glentig, Swaershoek, Alma, Waterberg Group, South Africa
Thesis (M. Sc. (Geology)) -- University of Limpopo, 2021
Keywords: Geology; Geochemistry; Glentig; Swaershoek; Alma; Waterburg Group; South Africa; Geochemistry; Formations (Geology) -- South Africa -- Limpopo; Geology -- South Africa -- Limpopo